KEHADIRAN SERANGGA PADA PERTANAMAN CAMPURAN KACANG GUDE DAN TOMAT - AMIR, MOH.; NOERDJITO, WORO A. (Research Center for Biology-Indonesian Institute of Sciences, 1986)
MOH. AMIR & WORO A. NOERDJITO, 1986.The presence insects on the intercrop plants of pigeonpeas and tomatoes. Berita Biologi 3(6): 268 -272.Intercropping system to reduce number of potential insect pests. However, the result will be vary depend on the appropriate component of the selected crops.The experiments using toniatoes as an intercrop of pigeonpeas was carried out at the HKTI (Himpunan Karya Tani Indonesia) garden at Tajur Bogor.The number of insect species as well as diversity in the intercropped pigeonpeas were compared with that in the pure stand of the same crops. The result indicated that number of insect species visited in the intercropped pigeonpeas was greater than in its pure culture.The number of insect species in the intercropped and pure pigeon peas increased with the increase of its developmental stages.The index diversity in the intercropped pigeonpeas were higher than that in its culture.